Back Cover: Dynamic Imaging of Ostwald Ripening by Environmental Scanning Transmission Electron Microscopy (ChemCatChem 22/2015). Issue 22 (November 2015) - Martin, Thomas E.; Gai, Pratibha L.; Boyes, Edward D.
Abstract : The Cover The cover depicts a twin lamellae within a Cu nanoparticle under 3 Pa of H2  at 250°C, imaged using an environmental TEM. In their Full Paper, Martin et al. report the first atomic resolution environmental scanning transmission electron microscope (ESTEM) study of nanoparticle sintering, which is shown to be governed by the Ostwald ripening mechanism. The importance of this is demonstrated by the significant enhancement in ripening rate of Cu nanoparticles in the presence of 3 Pa H2 . More details can be found in the Full Paper by Martin et al. onpage 3705 in Issue 22, 2015 (DOI:10.1002/cctc.201500830 ).